Regulating Cross-Border Data Flows in the Global Digital Economy: Comparative Perspectives from WTO, EU, and Indo-Pacific Frameworks - Zahoor Ahmed (INDONESIAN JOURNAL OF SUSTAINABILITY, 2026)
The rapid expansion of the digital economy has transformed international commerce by making cross-border data flows a fundamental component of global trade. Digital trade now encompasses a broad range of economic activities, including e-commerce, cloud computing, digital platforms, artificial intelligence services, and data-driven supply chains. While these developments have enhanced global economic integration and technological innovation, they have simultaneously generated complex legal and regulatory challenges relating to data privacy, cybersecurity, digital sovereignty, market access, and international trade governance. Divergent national and regional approaches to regulating cross-border data flows have contributed to increasing fragmentation within the global digital economy. This study examines the governance of digital trade through a comparative legal analysis of cross-border data regulation under the frameworks of the World Trade Organization (WTO), the European Union (EU), and emerging Indo-Pacific digital trade agreements.Employing a qualitative doctrinal and comparative legal methodology, the research analyzes the evolution of digital trade governance within multilateral, regional, and transnational legal frameworks. The study evaluates the WTO’s trade-oriented approach to digital commerce, the European Union’s comprehensive regulatory model for data protection and digital rights, and the flexible market-integration strategies adopted within Indo-Pacific digital trade agreements. Particular attention is given to the regulation of cross-border data flows, restrictions on data localization, privacy protections, cybersecurity obligations, and the institutional mechanisms developed to facilitate digital economic cooperation.The findings demonstrate that each regulatory framework reflects distinct legal philosophies and policy priorities. The WTO framework primarily emphasizes trade liberalization, market access, and non-discrimination principles but faces significant challenges in adapting existing trade rules to the rapidly evolving digital economy. The European Union adopts a rights-based regulatory model that prioritizes personal data protection, privacy, and digital sovereignty through comprehensive legal safeguards governing international data transfers. In contrast, Indo-Pacific digital trade agreements generally favor the facilitation of cross-border data flows and regional economic integration through flexible and innovation-oriented regulatory cooperation. These contrasting approaches highlight the continuing tension between economic openness and national regulatory autonomy in global digital trade governance.The study concludes that greater international coordination and legal harmonization are essential to reducing regulatory fragmentation and supporting sustainable growth in the global digital economy. Developing transparent and interoperable standards for cross-border data governance, strengthening international regulatory cooperation, and balancing trade liberalization with legitimate public policy objectives can contribute to a more coherent and effective framework for digital trade regulation. Such measures are necessary to ensure that the global digital economy remains open, secure, inclusive, and capable of fostering long-term economic development in an increasingly interconnected world.Keywords: Digital Trade; Cross-Border Data Governance; WTO; European Union; Indo-Pacific Trade Agreements.